1995
DOI: 10.1111/j.1365-2826.1995.tb00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Melanin‐Concentrating Hormone Gene Expression in Two Hypothalamic Nuclei of the Teleost Tilapia in Response to Environmental Changes

Abstract: For some teleosts, a role has been established for melanin-concentrating hormone (MCH) background adaptation and stress response. !n teleost fishes, prepro-MCH (ppMCH) mRNA is expressed in the hypothalamus, predominantly in neurons of the nucleus lateralis tuberis (NLT) and in scattered cells of the nucleus recessus lateralis (NRL). The response of mature tilapia to different environmental challenges was studied by assessing ppMCH mRNA levels in these two hypothalamic nuclei by quantitative dot blot analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Other reports have focused on the effects of environmental color on behavior (4,5,16), growth and survival (6). Effects of color background on chromatophore-regulating hormones have also been reported and Groneveld et al (17) found that the response of the melanin-concentrating hormone to background color is not strictly related to the pituitary-interrenal axis in tilapia. However, the present study supports the idea that color influences this axis, thus showing that color may affect different biological systems.…”
mentioning
confidence: 97%
“…Other reports have focused on the effects of environmental color on behavior (4,5,16), growth and survival (6). Effects of color background on chromatophore-regulating hormones have also been reported and Groneveld et al (17) found that the response of the melanin-concentrating hormone to background color is not strictly related to the pituitary-interrenal axis in tilapia. However, the present study supports the idea that color influences this axis, thus showing that color may affect different biological systems.…”
mentioning
confidence: 97%
“…It was proposed that MCH-ir neuronal somata were located only in the NLT from which axons projected to the pituitary, and that their synthetic activity was altered in response to the color of the environment Gröneveld et al 1995b;Suzuki et al 1995). However, a second group of parvocellular MCH neuronal somata has also been identified in the dorsal hypothalamus, located in the area above the LVR in the rainbow trout.…”
Section: Distribution Of Mch Neurons In the Brainmentioning
confidence: 99%
“…The finding that MCH interacts with the a-MSH cell not only has implications for our understanding of the roles of both cell types in background adaptation, but probably also for their func tions in the response to stressors. In tilapia, both cell types are responsive to acidification as a stressor ( 17,24), and in trout MCH secretion and biosynthesis are affected during injection and dis turbance stress (6,15).…”
Section: Effects Of Mch On the Release Of A-msh Isoformsmentioning
confidence: 99%
“…The antiserum is equally sensitive to des-, mono-and diacetyl a-MSH. Cross-reac tivity of the a-MSH antiserum with MCH [preliminary results have been reported by De Koning et al (13)] and MCH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) was assessed (see the Results section).…”
Section: A-msh Radioimmunoassaymentioning
confidence: 99%
See 1 more Smart Citation